2022
DOI: 10.1037/aap0000253
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies as moderators of COVID-19 racial discrimination in Filipino Americans.

Abstract: The present study examined the extent to which coronavirus disease 2019 (COVID-19) racial discrimination related to life satisfaction, depression, and anxiety in 246 Filipino Americans. The extent to which coping strategy moderated the mediated relationship of COVID-19 racial discrimination via depression and anxiety on life satisfaction was also explored. Findings indicated that Filipino Americans who experienced or witnessed COVID-19 racial discrimination were significantly more likely to experience decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
1
13
1
Order By: Relevance
“…Interestingly, inconsistent with prior literature (Litam & Oh, 2022), neither direct nor indirect coping styles moderated the relationship between racial discrimination and/or fear of discrimination and depression symptoms. These results highlight a potential difference between the two psychological distress variables, anxiety and depression symptoms, and the impact of coping styles.…”
Section: Discussioncontrasting
confidence: 92%
“…Interestingly, inconsistent with prior literature (Litam & Oh, 2022), neither direct nor indirect coping styles moderated the relationship between racial discrimination and/or fear of discrimination and depression symptoms. These results highlight a potential difference between the two psychological distress variables, anxiety and depression symptoms, and the impact of coping styles.…”
Section: Discussioncontrasting
confidence: 92%
“…The increase in racial discrimination against Asian Americans during the COVID-19 pandemic has also contributed to COVID-19 discrimination fear, which exacerbated mental health problems such as depression and anxiety (Cheng et al, 2021; Huang & Tsai, 2023; Litam & Oh, 2022a, 2022b). COVID-19 discrimination fear is defined as the fearful anticipation and expectation of discrimination (e.g., being harassed, not feeling safe in public) due to COVID-19-related concerns (i.e., potentially carrying the virus, being seen as Asian).…”
Section: Racial Discrimination and Covid-19 Discrimination Fearmentioning
confidence: 99%
“…Ethnic identity and other cultural factors may influence how Asian Americans cope with experiences of racial discrimination (Litam, 2020; Litam & Oh, 2021, 2022; Oh & Litam, 2022; Tweed & Conway, 2006). Coping strategies are behavioral and cognitive tactics that individuals utilize to deal with crises and stressful situations.…”
Section: Effects Of Racial Discrimination and Mental Healthmentioning
confidence: 99%
“…Experiences of COVID-19-related racial discrimination have been associated with greater rates of depression and anxiety and lower levels of life satisfaction among diverse AAPI ethnic subgroups, including Chinese and Chinese Americans (Litam & Oh, 2020), Filipino Americans (Litam & Oh, 2022), and international Asians residing in the U.S. (Litam et al, 2021). Despite the detrimental effect of COVID-19-related racism, some researchers have reported that higher levels of ethnic identity can buffer the impact of COVID-19 racial discrimination on life satisfaction for Chinese Americans (Litam & Oh, 2021) and that greater use of coping strategies reduced the mediated effects of racial discrimination via depression on life satisfaction for Filipino Americans (Litam & Oh, 2022). Despite the growing body of research on pandemic-related discrimination on the mental health and life satisfaction of AAPI ethnic subgroups, no empirical studies have been conducted to understand the impact of COVID-19-related racial discrimination on the mental health of Korean Americans (KA).…”
Section: Effects Of Racial Discrimination and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation